Can AI Predict Sudden Cardiac Death Risk? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Sudden cardiac death (SCD) is a devastating and often unforeseen event, accounting for a significant portion of cardiovascular mortality worldwide. For decad...
Keywords: AI in Cardiology; Predict; Sudden; Cardiac; Artificial Intelligence; Machine Learning; Deep Learning